Monitoring of the Visual System of Students in the Southern Region of Kazakhstan and the Implementation of the Results in the Methods of Teaching Biology - Aiman Beisembayevna Karabalayeva; Saltanat Zharylkasynovna Ibadullayeva; Abilova Sholpan Beisembaevna (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2021)
The deterioration of the health of the visual system of students, registered in modern conditions in the Republic of Kazakhstan, indicates the need to introduce constant monitoring of the health of the visual system of the younger generation living in poor environmental conditions. However, studies on monitoring the growth of eye diseases in students of the southern regions of Kazakhstan, which are necessary for conducting appropriate monitoring, are currently lacking. In this regard, the goal was set to conduct a study among students of biological specialties, as future teachers of biology, on the knowledge of the problems of the visual system as a basis for the subsequent introduction of a methodology to improve the dynamics of growth of eye diseases in students into the course of Human Physiology. Monitoring of the visual system of students, consisting of a questionnaire and a medical examination, revealed the attitude of students to their health and the main pathologies of the organ of vision.